New cultural histories of India : materiality and practices - Chatterjee, Partha; Guha-Thakurta, Tapati; Kar, Bodhisattva (Oxford University Press, 2014)
Most of the papers presented at the conference on 'New Cultural Histories of India', organized by Centre for Studies in Social Sciences during 5-7 January 2010.